Commerce in Nigeria 1968 : Volume 10 - Lagos Chamber of Commerce and Industry (Lagos : Lagos Chamber of Commerce and Industry, 1969)
This is the 1969 edition of the Commerce in Nigeria, a publication of the Lagos Chamber of Commerce and Industry which provides an annual examination the Nigerian economy. This edition covers: Kainji dam; the Nigerian economy; Nigerian External telecommunications; from bottleneck to modern Highway; business directory and an index of advertisers.
lje 21/1/19
Arch
Keywords: Commerce; Commerce; Nigeria